STEM CELL RESEARCH DEVELOPMENT AND ITS PROTECTION IN INDONESIA* - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research discusses the possibility of patenting stem cells under the Indonesian patent law by focusing on two essential issues: (a) what approaches should be chosen by the Indonesian government to protect stem cell research under the Indonesian Patent Act and non-patent regulations? and (b) what types of stem cells can be protected under the Indonesian Patent Act? In order to provide comparative perspectives, this paper discusses the experience and policies of the US, German and South Korean governments in protecting stem cell research under their patent acts.